Analysis of AHP and SAW Methods in a Decision Support System for Determining Employee Positions - Harianta Sembiring (Sean Institute, 2021)
Employees are an important asset for every company, because they greatly affect many aspects that determine the success of the company's work. A company will be able to run all its business processes well if all its employees can be well organized by the HR (Human Resources) section. Placement and utilization of resources in the right position is absolutely necessary. In this case, proper management and utilization of resources plays a very important role because it is a strategic approach to improving organizational performance. Determination of employee positions is still not effective because the job analysis in the employee placement section is not carried out properly so that employees do not know for sure the work he is doing in the company. In addition, many employees are not experts in the field of work they hold so that what they do on a daily basis is not in accordance with their abilities. From the results of the study, it can be concluded, among others: The application of a decision support system that was built can provide convenience and minimize errors that may occur in the process of determining employee positions. criteria for determining employee positions. The level of accuracy of the test results is 97%.